Pensamiento matemático de estudiantes de quinto grado cuando inventan y solucionan problemas (2024)
The article investigates the mathematical thinking manifested by fifth-grade students when they invent and solve mathematical problems. The research problem refers to the need for more knowledge of students' mathematical thinking and how it is usually undervalued when it is done through standardized tests. Knowing students' mathematical thinking helps to build study processes that recognize them. The research was conducted over one year; it is qualitative and naturalistic; invention and problem-solving wereused to determine students' mathematical thinking and solution strategies. The records were taken from the written production of forty-fifth graders when they invented problems to be proposed and solved by their classmates. The results report that children invent problems of an arithmetic nature, prefer operations between numbers over relations between them, and manifest difficulties in proposing problems when given information.